New BioRow developments - Kleshnev, V. (BioRow, 2021)
New BioRow method of data evaluation: A new template of biomechanical data evaluation has been developed for BioRow biomechanical measurements reports (Fig.1). In addition to comparison with Gold Standard Targets, there is now a statistical evaluation of each important indicator based on its group average and standard deviation (µ±s), which were obtained from the BioRow database (n>40k) for each boat type. As the measurements were taken from all rowers` levels, from beginners to Olympic champions, the data ranges were quite wide.